Fist welcomes new and returning students - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2009)
Gambang, July 2. FIST received its first batch of 51 Industrial Biotechnology and second batch of 58 Industrial Chemistry undergraduate students during MINDS week held at UMP's gateway campus in Gambang